1997
DOI: 10.1212/wnl.49.2.410
|View full text |Cite
|
Sign up to set email alerts
|

A volumetric MRI study of Gilles de la Tourette's syndrome

Abstract: The neuroanatomic or neuropathologic basis of Gilles de la Tourette's syndrome (GTS) remains unknown. Recent studies have suggested abnormalities of cerebral asymmetry and basal ganglia volumes. We studied 17 patients with GTS and eight normal controls using volumetric MRI techniques for measuring the caudate nucleus, amygdala, and corpus callosum. One subject with GTS was subsequently excluded because he was left handed. No absolute differences in caudate nucleus volumes between patient and control groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 12 publications
6
48
1
Order By: Relevance
“…Several structural studies have reported that either the caudate or the lenticular nuclei are abnormal in volume or asymmetry compared with control subjects. [82][83][84] Because TS is more common in boys than in girls by a ratio of at least 3:1, most research has focused on male subjects, thereby limiting our knowledge of TS in girls. Using methodologies that previously identified structural abnormalities in young male TS patients, Zimmerman et al 85 showed that basal ganglia volume and asymmetry differences did not distinguish girls with TS from matched control subjects.…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several structural studies have reported that either the caudate or the lenticular nuclei are abnormal in volume or asymmetry compared with control subjects. [82][83][84] Because TS is more common in boys than in girls by a ratio of at least 3:1, most research has focused on male subjects, thereby limiting our knowledge of TS in girls. Using methodologies that previously identified structural abnormalities in young male TS patients, Zimmerman et al 85 showed that basal ganglia volume and asymmetry differences did not distinguish girls with TS from matched control subjects.…”
Section: Morphologymentioning
confidence: 99%
“…Similarly, the corpus callosum has been previously shown in MRI studies to be abnormal in individuals with TS, predominantly males. 83,86,87 Once again, a study designed to examine whether abnormalities in corpus callosum morphology were also present in girls with TS failed to show a significant difference. 88 The aforementioned studies do not imply that the findings in males with TS were invalid, but rather point out that there are gender differences in the neurobiologic manifestations of TS.…”
Section: Morphologymentioning
confidence: 99%
“…Most of the existing structural neuroimaging studies on TS were on the basal ganglia, corpus callosum, and lateral ventricle (4)(5)(6)(7)(8)(9)(10). Functional neuroimaging studies of TS using positron emission tomography (PET) suggest that the cortical system (especially, the frontal lobe area) is related with the pathophysiology of TS (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…MRI assessment of PANDAS youth has demonstrated enlarged basal ganglia (Giedd et al 1996(Giedd et al , 2000, and positron emission tomography has demonstrated increased activated microglial cells, which are suggestive of neuroinflammation, in bilateral caudate nuclei and bilateral lentiform in youth with PANDAS (Kumar et al 2014). The basal ganglia have also been implicated in pediatric OCD (Rosenberg et al 1997;Szeszko et al 2004) and tic disorders (Moriarty et al 1997;Peterson et al 2003;Amat et al 2006).…”
Section: Discussionmentioning
confidence: 99%